Maternal positive coparenting and adolescent peer attachment: Chain intermediary role of parental involvement and parent–child attachment - Ji, Wanghua; Yang, Yang; Han, Ying; Bian, Xiaohua; Zhang, Yunhong; Liu, Junqi (Frontiers in Psychology, 2022)
This study investigated the relationship between maternal positive coparenting and adolescent peer attachment, and the intermediary role of parental involvement and parent–child attachment in 1,807 families using the maternal positive coparenting scale, the parental involvement scale, and the parent and peer attachment scale. The results showed that maternal positive coparenting behaviour, parental involvement, parent–child attachment, and peer attachment had significant positive relationships, and maternal positive coparenting had a positive correlation with adolescent peer attachment. Moreover, parental involvement and parent–child attachment played a significant mediating role between maternal positive coparenting behavior, including unity and consistent behavior, and adolescent peer attachment, respectively, which consisted of a sole intermediary role of parental involvement; a single intermediary role of parent–children attachment; and a chain intermediary role of parental involvement and parent–children attachment. Hence, maternal positive coparenting was positively associated with adolescent peer attachment, in which parental involvement and parent-child attachment served as a crucial bridge.